Training a New Generation for Careers in Wildlife Management in Ethiopia - Murali Pai; Takele K. Serekebirhan (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2016)
This article describes the start-up of a new interdisciplinary Master's program in Wildlife Management at Arba Minch University (AMU), Ethiopia. The need, salient features, review of curriculum, and stakeholders of the program are examined. The human dimensions of wildlife management have been given its due with an aim to get biodiversity stewardship on a firm footing in the country. The program, aims to link young graduates to regional stakeholders on conservation perspectives through courses such as Human Dimensions of Wildlife Management, Wildlife Economics and Entrepreneurship and Biodiversity Conservation. The scope of wildlife tourism in Ethiopia has been highlighted in the program. The survey results of stakeholder representatives found good prospects for the sustainability of the MSc program in wildlife management provided stakeholder coordination and community participation in the program are diligently ensured. In conclusion, the Master's program in wildlife management is interdisciplinary, job-oriented and intended to prepare a new generation for placements with the government, NGOs and private sector in order to contribute to wildlife management and biodiversity stewardship in Ethiopia